PENGARUH INTERAKSI SOSIAL TEMAN SEBAYA TERHADAP PERILAKU MORAL PESERTA DIDIK KELAS XI DI SMA NEGERI 1 LUHAK NAN DUO KABUPATEN PASAMAN BARAT - Sindy Fathonah; Mori Dianto; Fuaddillah Putra (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research is motivated by the cases of bad attitude students. they are talkedwith the harsh words to the friends. Like used bad words, and oppose theteachers. The study used qualitative research methods. The population in thisresearch is 69 of students. The sampling technique is total sampling. Theinstrument used in this research was a questionnaire. Data analysis in this study ispercentage and simple linear regression. The results of this research is: 1). socialinteraction of students in the XI class at SMA Negeri 1 Luhak Nan Duo KabupatenPasaman Barat is in the high category,2). Moral behavior of students in the XIclass at SMA Negeri 1Luhak Nan Duo Kabupaten Pasaman Barat is in the highenough. There are influence social interaction of friends to moral behavior ofstudents in the XI class at SMA Negeri 1 Luhak Nan Duo Kabupaten PasamanBarat is very low coefficients with the value is 0,185. Based on the results of thisstudy is recommended for the students to improve the aspects of social interactionwith friends, such as actively participate in school activities, like extra moreactivities at the school, and participate in group discussion at the class, andparticipate for events at the school.